Colonial residue: REDD+, territorialisation and the racialized subject in Guyana and Suriname - Collins, Yolanda Ariadne (Geoforum, 2019)
•Introduces colonial residue as continued colonial presence with which REDD+ engages.•Parses out impact of colonial residue on REDD+.•Explores continuities between colonial forest management and REDD+.•Focuses on legibility & visibility of land management practices and subjectivities.•Demonstrates how REDD+ is a continued colonial land claim across states. In this paper, I argue that the Reducing Emissions from Deforestation and forest Degradation (REDD+) mechanism, a globally driven, market-based environmental policy, is racialized in practice. Yet, consideration of how the uptake of these policies is challenged by racialized relations is insufficiently addressed in the neoliberal conservation literature. Colonial histories are sedimented in racialized subjectivities and land management practices where certain economic activities, geographical sites and interactions with the natural environment became the stronghold of different groups. In this paper, I demonstrate how the Reducing Emissions from Deforestation and forest Degradation (REDD+) mechanism, one such globally driven, market-based environmental policy, is challenged by the legacy of these racialized land use practices and social relations rooted in the defining colonial period in Guyana and Suriname. I outline the relationship between the processes of politically demarcating forests and of shaping subjectivities, drawing attention to how these processes are impacted by REDD+. Through a focus on gold mining, explored here as a historically conditioned, economic relationship with the natural environment, I show how REDD+ contributes to state territorialisation, complicates pre-existing racialized subjectivities and increases the legibility of forests and their amenability to state management.